2019
DOI: 10.1002/aps3.11254
|View full text |Cite
|
Sign up to set email alerts
|

A customized nuclear target enrichment approach for developing a phylogenomic baseline for Dioscorea yams (Dioscoreaceae)

Abstract: Premise We developed a target enrichment panel for phylogenomic studies of Dioscorea , an economically important genus with incompletely resolved relationships. Methods Our bait panel comprises 260 low‐ to single‐copy nuclear genes targeted to work in Dioscorea , assessed here using a preliminary taxon sampling that includes both distantly and closely related taxa, including several yam crops and potential crop wild … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 80 publications
3
58
0
Order By: Relevance
“…The most common design for target sequence capture in plants involves developing probes that target low‐copy orthologous loci from a narrow set of in‐group taxa (Gardner et al., ; Vatanparast et al., ; Villaverde et al., ; Soto Gomez et al., ). Alternatively, universal gene sets that work across a wider variety of taxa have also been developed; for example, in Compositae (Mandel et al., ), Bryophyta (Liu et al., ), ferns (Wolf et al., ), or flowering plants (Buddenhagen et al., ; Johnson et al., ).…”
Section: Comparison Of Consumable Costs Between Conventional and Low‐mentioning
confidence: 99%
See 1 more Smart Citation
“…The most common design for target sequence capture in plants involves developing probes that target low‐copy orthologous loci from a narrow set of in‐group taxa (Gardner et al., ; Vatanparast et al., ; Villaverde et al., ; Soto Gomez et al., ). Alternatively, universal gene sets that work across a wider variety of taxa have also been developed; for example, in Compositae (Mandel et al., ), Bryophyta (Liu et al., ), ferns (Wolf et al., ), or flowering plants (Buddenhagen et al., ; Johnson et al., ).…”
Section: Comparison Of Consumable Costs Between Conventional and Low‐mentioning
confidence: 99%
“…() recovered 150 protein‐coding nuclear genes across mosses (Bryopsida) using 96 libraries multiplexed in a single myBaits reaction. However, pooling strategies using 24–48 libraries per myBaits reaction are more common (e.g., Johnson et al., ; Villaverde et al., ; Soto Gomez et al., ; Zerega and Gardner, ).…”
Section: Hybridization and Enrichmentmentioning
confidence: 99%
“…Other recent studies have also demonstrated the efficacy of taxon-specific probe sets in resolving species-level relationships from herbarium DNA (Finch et al, 2019;Soto Gomez et al, 2019;White et al, 2019). Whereas Kadlec et al (2017) argued that high sequence variability across angiosperm orders precluded the usefulness of universal probes in resolving species-level relationships, Chau et al (2018) found that general purpose probes can be as effective as taxon-specific ones.…”
Section: Efficacy Of Universal Probesmentioning
confidence: 99%
“…The increasing availability of genomic and transcriptomic data across the tree of life and the accessibility of pipelines to identify potential orthologs with low or single copy number ( Chamala et al., 2015 ; Faircloth, 2016 ) help support the design of clade-specific bait sets ( e.g. Vatanparast et al., 2018 ; Finch et al., 2019 ; Soto Gomez et al., 2019 ). Larridon et al.…”
Section: Introductionmentioning
confidence: 99%